2015
DOI: 10.1111/jdi.12321
|View full text |Cite
|
Sign up to set email alerts
|

Association between the level of circulating adiponectin and prediabetes: A meta‐analysis

Abstract: Aims/IntroductionAdiponectin has been proposed to have an essential role in the regulation of insulin sensitivity and metabolism, but previous studies on levels of adiponectin in prediabetes remain inconsistent. The present study aimed to assess the differences of adiponectin levels between prediabetes patients and healthy controls by carrying out a meta-analysis.Materials and MethodsWe carried out a systematic literature search of PubMed, EMBASE, and other databases for case–control studies and cohort studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
4
15
1
Order By: Relevance
“…In the normal condition, the circulating adiponectin serum levels are high in contrast to the low level of other adipocytokines 29 . In line with other studies [30][31][32][33][34][35] , the present study also showed that adiponectin levels were significantly decreased in patients with type 2 diabetes mellitus compared with individuals without type 2 diabetes mellitus. In addition, decreased adiponectin levels observed in overweight individuals supports the fact that adiponectin serum levels were inversely correlated with obesity, especially with the accumulation of visceral fat 33 .…”
Section: Discussionsupporting
confidence: 93%
“…In the normal condition, the circulating adiponectin serum levels are high in contrast to the low level of other adipocytokines 29 . In line with other studies [30][31][32][33][34][35] , the present study also showed that adiponectin levels were significantly decreased in patients with type 2 diabetes mellitus compared with individuals without type 2 diabetes mellitus. In addition, decreased adiponectin levels observed in overweight individuals supports the fact that adiponectin serum levels were inversely correlated with obesity, especially with the accumulation of visceral fat 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, due to the observational nature of our study, it remains to be elucidated whether the observed associations are causal. While experimental and animal studies clearly point towards insulin‐sensitizing properties of adiponectin, MR studies yielded mixed evidence regarding a causal role of adiponectin in the development of insulin resistance and type 2 diabetes . In line with the weak associations seen for hsCRP in the present analysis, a large previous MR study concluded that associations between CRP and insulin resistance, glycaemia and diabetes are most likely noncausal .…”
Section: Discussionsupporting
confidence: 47%
“…Another important marker for the prediabetic condition is the low level of adiponectin, an adipokine that plays a crucial role in insulin sensitivity and regulation of glucose metabolism, and is also considered a risk factor for cardiovascular disease (Banerjee et al, 2017;Lai, Lin, Xing, Weng, & Zhang, 2015). Previous studies showed citrus flavonoids positively regulate adiponectin transcription in adipocytes and increase their levels in patients with myocardial infarction (Haidari et al, 2015;Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%